The Role of Jump Rope Game in Developing Early Childhood Cooperation Skills - Safitri, Dahrul (Al-Athfal: Jurnal Pendidikan Anak, 2023)
Purpose – The proliferation of modern games has gradually eroded the existence of traditional games rich in essential cooperation values for children from an early age. This research aims to analyze the traditional jump rope game as a means to develop early childhood cooperation skills, amidst the prevalence of modern games that emphasize individualism. Design/methods/approach – This research employs a qualitative approach through a case study. Data collection involves observation, interviews, and documentation. The data analysis technique used follows Miles and Huberman's concept, including data reduction, data presentation, and conclusion drawing. The research informants consist of five parents of children aged 5-6 years, with three boys and two girls as research subjects. Data validity is ensured through source triangulation. Findings – The jump rope game, commonly known as "lompat karet" due to the use of rubber as the rope in Dukuh Sewelut, demonstrates various positive attributes related to early childhood cooperation skills and positive effects on children's cooperative abilities. Research implications/limitations – This research has limitations, and its results are not intended to provide general conclusions. However, it is expected that this research can be used to understand similar phenomena. Practical implications – The findings of this research are expected to enhance our understanding of the importance of traditional jump rope games in building and nurturing early childhood cooperation skills. Originality/value – Future research will delve into traditional games that can enhance self-regulation skills in children and explore the deeper negative impacts of traditional games.   Paper type Case study